Generalized Bessel function of Type D - Demni, N. (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
We write down the generalized Bessel function associated with the root system of type D by means of multivariate hypergeometric series. Our hint comes from the particular case of the Brownian motion in the Weyl chamber of type D.